Constructing Two-Dimensional (2D) Heterostructure Channels with Engineered Biomembrane and Graphene for Precise Scandium Sieving - Liang, Jing (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.